Polyols accumulated in ribose‐5‐phosphate isomerase deficiency increase mitochondrial superoxide production and improve antioxidant defenses in rats' prefrontal cortex. Issue Volume 37:Issue1(2014:Oct.) (23rd June 2014) - Stone, V.; Kudo, K.Y.; August, P.M.; Marcelino, T.B.; Matté, C.
Abstract: The ribose‐5‐phosphate isomerase deficiency is an inherited condition, which results in cerebral d ‐arabitol and ribitol accumulation. Patients present leukoencephalopathy, mental retardation, and psychomotor impairment. Considering that the pathophysiology of this disorder is still unclear, and literature are sparse and contradictory, reporting pro and antioxidant activities of polyols, the main objective of this study was to investigate some parameters of oxidative homeostasis of prefrontal cortex of rats incubated with d ‐arabitol and ribitol. We found evidences that ribitol promoted an increase in antioxidant enzymes activity (superoxide dismutase, catalase, and glutathione peroxidase), probably secondary to enhanced production of superoxide radical, measured by flow cytometry. Oxidation of proteins and lipids was not induced by polyols. Our data allow us to conclude that, at least in our methodological conditions, arabitol and ribitol probably have a secondary effect on the pathophysiology of ribose‐5‐phosphate isomerase deficiency.